Physiological changes induced by green fodder expansion into grasslands and croplands enhance water-use efficiency in the Northeastern Tibetan Plateau - Xu Wang; Jilin Yang; Jie Wang; Tong Yang; Chuchen Chang; Yanbo Zhao; Xiaocui Wu; Geli Zhang; Xiangming Xiao (Agricultural Water Management)
The rapid green fodder expansion in native grassland and cropland in the northeastern Tibetan Plateau (a rain-fed region), driven by the increasing forage demand, has altered vegetation patterns and potentially affected carbon and water cycles. To clarify the elusive effects of green fodder expansion on the carbon sequestration and water consumption in this region, we examined its impacts on productivity, evapotranspiration, and water-use efficiency using a pairwise comparison approach at seasonal and annual scales in 2019. We also conducted an attribution analysis to undercover the mechanisms through which green fodder expansion influences water-use efficiency. Our results revealed that during the growing season, gross primary productivity in green fodder lands was 12.25 % and 4.14 % higher than the adjacent grasslands and croplands, respectively. Evapotranspiration was 2.89 % and 3.33 % lower in comparison. Ecosystem-level water-use efficiency was respectively 15.14 % and 6.92 % higher, while plant-level water-use efficiency increased by 4.76 % and 1.5 %, respectively. Green fodder expansion enhanced ecosystem-level water-use efficiency by increasing gross primary productivity and reducing evapotranspiration, while improvements in plant-level water-use efficiency were mainly driven by gross primary productivity increases. The changes in plant physiology and canopy structure induced by green fodder cultivation enhanced the CO2 assimilation capacity, reduced soil evaporation, and allocated more water toward transpiration, emerging as the dominant factors driving the observed changes in gross primary productivity and evapotranspiration. However, we found that green fodder planting also led to increased soil evaporation over the non-growing season, which partially offset its positive effect on water-use efficiency during the growing season. This study suggests that green fodder cultivation could be a potential solution to increasing forage supply in the northeastern Tibetan Plateau, while highlighting the necessity of reducing soil evaporation during the non-growing season to maximize the benefits of green fodder expansion.